Effective Learning Guidance Program in Improving the Calistung Ability of Children Aged 5-10 Years in Sudipayung Village - Hari Ananda Saputra; M Fathin Fada; Ishmatu Amri; Muhammad Afwan Yazyd; Nurul Alifah; Hani Darayani Inasa; Alfarida Paramita Ayu Setyorini (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
Calistung is a learning activity carried out by children by writing or drawing on layers of paper orother media spread on the floor. The calistung method aims to develop children's fine motor skills, such as the ability to write, draw, and recognize letters or numbers. CaLisTung can also help children develop cognitive and social skills, such as recognizing colors and shapes and interacting with peers. This service was carried out in Sudipayung Village, Ngampel District, and Kendal Regency. Parti cipants in this program are child renat the elementary school evelin Tanjung Asri Village, with a total of 25 children. The results of the implementation of this service show that the use of the method Calistung students have literacy skills such as reading, writing, and arithmetic. This kind of activitycan create beneficial changes by improving their literacy skills. increases student engagement inlearning and has a positive impacton their emotional as pects, knowledge, and behavior.